Recent Advancement in Drug Targeting Therapies in the Treatment of Pancreatic Cancer - Harwansh, Ranjit K.; Hamid, Junainah Abd; Wal, Pranay; Deshmukh, Rohitas; Patra, Pratap Kumar; Gasmi, Amin (Current Pharmaceutical Design, 2025)
Objective of the StudyThis review aims to critically analyze the scope for targeting drugs towards the treatment of improving outcomes in PDAC, focusing on DNA repair inhibitors, antiangiogenic therapy, inhibitors of the KRAS pathway, anti-stromal, and nanoparticle-based therapy.Materials and MethodsA critical review of preclinical and clinical studies was conducted to summarize the therapeutic interventions that target specific mutations in PDAC, components of the tumor microenvironment, and drug delivery systems, especially nanotechnology, to enhance targeting and efficacy.ResultsInhibitors and nanotechnology-based targeted therapies have reported promise in preclinical models: drug delivery is enhanced with the loss of PDAC resistance mechanisms. Formulations and combinations targeting KRAS as well as other pathways point toward improved drug delivery over 'orthodox' treatment approaches.ConclusionThis review concludes that although improvement in therapies for PDAC has incrementally been proven in recent literature, however, more research is expected to enhance these approaches so that they can be applied appropriately at the clinical stage. In future studies, it is expected to optimize treatment combinations, address mechanisms of resistance, and improve the delivery of drugs.
Keywords: targeted therapy